2001
DOI: 10.1111/j.1574-0862.2001.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Marketing cooperatives and financial structure: a transaction costs economics analysis

Abstract: The relationship between the financial structure of a marketing cooperative (MC) and the requirement of the domination of control by the members is analysed from a transaction costs perspective. A MC receives less favourable terms on outside equity than a conventional firm because the decision power regarding new investments is not allocated to the providers of these funds. This is a serious threat to the survival of a MC in a market where efficient investments are characterised by an increasing level of asset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…94-103, 390-391). Cooperation among farmers is explained by the economies of scale and the effort of minimizing transaction costs [5,8,51]. If one or both of these purposes is met, collective action benefits farmers.…”
Section: Systems Approach To Dynamic Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…94-103, 390-391). Cooperation among farmers is explained by the economies of scale and the effort of minimizing transaction costs [5,8,51]. If one or both of these purposes is met, collective action benefits farmers.…”
Section: Systems Approach To Dynamic Complexitymentioning
confidence: 99%
“…A larger membership allows an increment of both productive capital and stock of reputation, which produces benefits from collective action, yet it takes some time before this influence can be realized (Figure 1). Cooperation among farmers is explained by the economies of scale and the effort of minimizing transaction costs [5,8,51]. If one or both of these purposes is met, collective action benefits farmers.…”
Section: Systems Approach To Dynamic Complexitymentioning
confidence: 99%
“…He argues that in the course of time with changing general economic and market environment, the TAMCs in West Europe gradually adapted their goal of realising a maximum price for the products supplied by farmer-members into the more general goal of a satisfactory income and continuity of business (marketing, processing). Meulenberg (1978) also showed that marketing instruments to achieve the TAMCs' objectives are the same as for investor firms, however, the internal governance of cooperatives might considerably limit their efficient use (see also Hendrikse and Veerman 2000;Krol et al 2010).…”
Section: Strategies and Effects Of Milk Producers' Organisations In Tmentioning
confidence: 99%
“…Bonus (1986, p335) summarizes his position as 'The cooperative association is a hybrid organizational mode …', although he states later on the same page that '… a firm jointly owned by the holders of transaction-specific resources …'. Hendrikse and Veerman (2001) classify a cooperative as a hierarchy. 9 We agree with Sexton (1984, p429) when he writes 'Labor-managed firms are closely analogous to agricultural marketing cooperatives.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%